2014
DOI: 10.15439/2014f39
|View full text |Cite
|
Sign up to set email alerts
|

Social media and emotions in organisational knowledge creation

Abstract: Social media increases the connectivity of people inside and outside an organisation. It is not just the implementation of communication technology, but the transformation of working and organisational cultures. The paper presumes that social media provides new opportunities to the organisational knowledge creation process by amplifying knowledge created by individuals as well as crystallising and connecting it to an organisation's knowledge system. The process depends fundamentally on the individual's tacit k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 72 publications
(93 reference statements)
0
6
0
5
Order By: Relevance
“…Also in other studies Social media can be showed asfeatures, content, means, people and purpose (Jalonen, 2014(Jalonen, , 1372.…”
Section: Social Mediamentioning
confidence: 98%
“…Also in other studies Social media can be showed asfeatures, content, means, people and purpose (Jalonen, 2014(Jalonen, , 1372.…”
Section: Social Mediamentioning
confidence: 98%
“…Knowledge is a significant asset for any organization and is vital for its competitive advantage (Jalonen, 2014). Employees using the Internet and Information and Communication technologies such as SNSs enhanced organizational knowledge through employee collaboration and knowledge sharing.…”
Section: Interpreting the Findings In The Context Of Wider Published Literaturementioning
confidence: 99%
“…customer care and product feedback) (Broughton et al, 2009). The connectivity of employees using SNSs within and across organizations and with customers generate a large amount of big data, which can be interpreted to create useful knowledge for leaders involved in organizational strategic decision making, innovation, and marketing (Jalonen, 2014).…”
Section: Interpreting the Findings In The Context Of Wider Published Literaturementioning
confidence: 99%
“…Media sosial secara umum mengacu pada alat interaksi antar manusia yang berbasis komputerisasi dimana setiap orang dapat bertukar informasi di dalamnya melalui internet, media sosial merupakan wadah yang mampu menuatkan teknologi, manusia, dan informasi (Jalonen, 2014). Badan Pusat Statistik (BPS) bekerjasama dengan Asosiasi Penyelenggara Jasa Internet Indonesia (APJII) mencatat angka pertumbuhan pengguna internet di Indonesia hingga akhir tahun 2013 mencapai 71,19 juta orang, meningkat pada tahun 2014 mencapai 83,7 juta orang (Rahayuning, 2009).…”
Section: Pendahuluanunclassified